Effects of balanced hydroxyethyl starch 6% (130/0.4) and albumin 5% on clot formation and glycocalyx shedding: Subgroup analysis of a prospective randomized trial. Issue 183 (November 2019) - Kammerer, Tobias; Hulde, Nikolai; Speck, Eike; Hübner, Max; Crispin, Alexander; Zwissler, Bernhard; Conzen, Peter; von Dossow, Vera; Schäfer, Simon Thomas; Hofmann-Kiefer, Klaus; Rehm, Markus
Abstract: Background: Intravenous fluids can impair coagulation and affect the endothelial glycocalyx, whereas glycocalyx shedding itself can cause an impairment of clot formation and firmness. We hypothesized that hydroxyethyl starch 6% (130/0.4) has a more distinct effect on coagulation and glycocalyx shedding than albumin 5%. Methods: Presented data derive from an exploratory subgroup analysis of a prospective randomized, single-blinded trial comparing albumin 5% versus balanced hydroxyethyl starch 6% (130/0.4). Patients between 46 and 85 years undergoing cystectomy were included. Prothrombin time, plasma fibrinogen concentration, partial thromboplastin time, thrombelastometry and platelet function were analyzed before and after surgery. Glycocalyx components were assessed before and after surgery, 2 to 4 h after surgery and at 1st and 3rd postoperative day. Primary outcome parameter was the change of thrombelastometric variables at the end of surgery. Further variables included calculated blood loss, infusion amount and transfusion rate. Results: 55 patients (albumin group n  = 28; hydroxyethyl starch group n  = 27) were included. Thrombelastometric variables were significantly more compromised in the hydroxyethyl starch than in the albumin group whereas platelet function, glycocalyx shedding, partial thromboplastin time, prothrombin time and fibrinogen were not different between groups. Mean intraoperative calculated blood loss was higher in the hydroxyethyl starch group (1557 ± 825 ml versus 1245 ± 709 ml; p = 0.042). Transfusion requirements did not differ. Conclusion: Rotational thrombelastometric variables were significantly more reduced when hydroxyethyl starch was used compared to albumin 5%. This effect was independent from a shedding of the endothelial glycocalyx. However, results presented here are from a subgroup analysis and must be considered with caution. Trial registration EudraCT number 2010-018343-34. Highlights: Intravenous fluid therapy can impair clot formation and cause glycocalyx shedding. Subgroup analysis of a randomized trial comparing albumin 5% and hydroxyethyl starch 6%. Hydroxyethyl starch impairs thrombelastometric parameters more than albumin 5%. Glycocalyx shedding was not associated with reduced clot formation or platelet function.